Selective nerve fibre activation in patients with generalized chronic pruritus: hint for central sensitization? - Pereira, Manuel P.; Agelopoulos, Konstantin; Köllner, Johannes; Neufang, Gitta; Schmelz, Martin; Ständer, Sonja (Acta dermato-venereologica, 2019)
Central sensitization induces pain augmentation in chronic pain states. An analogous mechanism is speculated for chronic pruritus. This study compared patients with chronic pruritus (n = 79) of different origins (atopic dermatitis, chronic pruritus on non-lesional skin, chronic prurigo) and healthy controls (HC, n = 54) with regard to itch intensity and qualities of sensory symptoms after selective peripheral nerve fibre activation by electrical stimulation at 5 Hz (surrogate for C-fibre function) and 2,000 Hz (surrogate for Aβ-fibre function) using a Neurometer®. Electrically-induced itch was more intense in patients with chronic pruritus than in HC, but patients with chronic pruritus did not report "itch" more often than HC at 5 Hz. Stimulation at 2,000 Hz induced more pricking and tingling, but less throbbing in patients with chronic pruritus compared with HC. Treatment with cooling compound reduced clinical and experimental itch, but did not alter the distribution of sensory symptoms. These data show hyperknesis in chronic pruritus of various origins, arguing for common central sensitization mechanisms.
Gesehen am 11.11.2019